Knowledge, attitudes, and practices regarding exercise management among patients with primary hypertension: a cross-sectional study - Yunjin Liu; Jian Yao (Scientific Reports)
Abstract A study conducted in 2024 at two healthcare centers evaluated exercise management knowledge, attitudes, and practices among patients with primary hypertension using a questionnaire (Cronbach’s α = 0.838). Analysis of 550 valid questionnaires revealed mean knowledge, attitude, and practice scores of 4.54 ± 1.03 (/8, 56.75%), 35.40 ± 8.12 (/45, 78.67%), and 24.38 ± 4.84 (/45, 69.66%), indicating insufficient knowledge, positive attitudes, and suboptimal practices. Non-medical occupation (OR 0.418, 95% CI 0.176–0.995, P = 0.049), monthly income of 5000–10,000 CNY (OR 3.263, P = 0.006) and > 10,000 CNY (OR 3.927, P = 0.011), hypertension diagnosis for 3–5 years (OR 0.591, P = 0.036), and diabetes (OR 0.573, P = 0.042) were associated with knowledge. Age (OR 0.934, P < 0.001), hypertension diagnosis for > 5 years (OR 11.985, P < 0.001), and regular exercise (> 1 h/day, OR 19.102, P < 0.001; every 2–3 days, OR 69.112, P < 0.001; every 4–5 days/week, OR 0.289, P = 0.016; every 6–7 days/week, OR 0.020, P < 0.001) were associated with attitude. Attitude scores (OR 1.457, P < 0.001), age (OR 0.959, P = 0.004), education level (high school/technical school, OR 0.407, P = 0.049; bachelor’s degree or above, OR 0.381, P = 0.046), hypertension diagnosis for 3–5 years (OR 2.426, P = 0.032), infrequent blood pressure monitoring (OR 0.152, P < 0.001), and regular exercise (> 1 h/day, OR 5.827, P = 0.001; every 2–3 days, OR 10.280, P < 0.001; every 4–5 days/week, OR 12.267, P < 0.001) were associated with practice. In summary, patients with hypertension in Baotuquan demonstrate insufficient knowledge, positive attitudes, and suboptimal practices regarding exercise management.